A Hemodynamic Study to Evaluate the Buffer Response in Cirrhotic Patients Undergoing Liver Transplantation. (17th March 2014) - Anders, Margarita; Alvarez, Daniel; Quiñonez, Emilio; Orozco, Federico; Goldaracena, Nicolas; McCormack, Lucas; Mastai, Ricardo
Abstract : The physiological regulation of the liver blood flow is a result of a reciprocal portal vein and hepatic artery flow relationship. This mechanism is defined as the hepatic arterial buffer response (HABR). This study was addressed to investigate whether HABR is maintained in denervated grafts in liver transplant recipients. Portal blood flow (PBF) and hepatic arterial resistance index (PI) were measured 6 months after transplantation using Doppler. In each patient we consecutively measured the vasodilator (Ensure Plus PO versus placebo) and vasoconstrictor (isosorbide dinitrate 5 mg SL versus placebo) stimuli. The meal ingestion caused a significant increase of both parameters, PBF (from 1495 ± 260 to 2069 ± 250 mL/min, P < 0.05 ) and PI (from 0.7 ± 0.2 to 0.8 ± 0.2, P < 0.05 ). By contrast, isosorbide dinitrate reduced PBF (from 1660 ± 270 to 1397 ± 250 mL/min, P < 0.05 ) and PI (from 0.7 ± 0.2 to 0.5 ± 0.2, P < 0.05 ). We show that PBF and PI are reciprocally modified with the administration of vasoconstrictor and vasodilator stimuli. These results suggest the persistence of the HABR in a denervated human model, suggesting that this mechanism is independent of the regulation from the autonomic nervous system.